MANAGEMENT OF SITZ BATH AND DECORATED PURPLE LEAVES FOR ACUTE PAIN PROBLEMS IN HEMORRHOID PATIENTS - ARIYANTO, MIFTAH PUTRI; SUSANTO, BELA NOVITA AMARIS; SETIYANINGSIH, RATNA (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
Hemorrhoids are an anorectal disease which is defined as enlargement of the hemorrhoidal veins that pass through the anus or rectum, which is caused by abnormal widening and distortion of the vascular channel, along with destructive changes in the supporting connective tissue in the anus, causing pain and discomfort. And causes bleeding after defecation. Management of sitz baths and administration of purple leaf decoction. Describe the management of acute pain: sitz baths and administering purple leaf decoction to hemorrhoid patients. The design of this research is descriptive qualitative: a case study using the nursing process. The sampling technique used in this research uses non-probability sampling with a purposive sampling approach. The samples taken were 3 subjects. The subject’s assessment data stated that pain in the anus and pain due to hemorrhoidal lumps were like being pricked with a pain scale of 4-6, felt intermittent or sometimes continuous, the subject’s expression grimaced in pain, the subject’s face looked tense, occasionally the subject held his anus, the subject could not sitting for too long and when sitting the subject often changes sitting position, there is a soft solid lump in the anus, the color of the lump is reddish. The nursing diagnosis is acute pain related to inflammation (hemorrhoids). Researchers carried out nursing actions for 7 days with 14 meetings. The last evaluation showed complaints of decreased pain, decreased grimaces, decreased anxiety. Management of sitz baths and administration of purple leaf decoction to hemorrhoid patients is effective in reducing the level of pain in hemorrhoid patients.